Current State of Investment Activity of Oil and Gas Companies of Uzbekistan and its Specific Tendencies - Abdushukrovna, Bakieva Iroda (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
In the article is considered the issues related to the assessment of the current state of investment activities of oil and gas companies in the Republic, the identification of specific tendencies in the sphere, and provided relevant conclusions.